Genome-wide analysis of the PreA/PreB (QseB/QseC) regulon of Salmonella enterica serovar Typhimurium - Merighi, Massimo (BioMed Central, 2009)
BACKGROUND: The Salmonella PreA/PreB two-component system (TCS) is an ortholog of the QseBC TCS of Escherichia coli. In both Salmonella and E. coli, this system has been shown to affect motility and virulence in response to quorum-sensing and hormonal signals, and to affect the transcription of the Salmonella enterica serovar Typhimurium (S. Typhimurium) pmrAB operon, which encodes an important virulence-associated TCS. RESULTS: To determine the PreA/PreB regulon in S. Typhimurium, we performed DNA microarrays comparing the wild type strain and various preA and/or preB mutants in the presence of ectopically expressed preA (qseB). These data confirmed our previous findings of the negative effect of PreB on PreA gene regulation and identified candidate PreA-regulated genes. A proportion of the activated loci were previously identified as PmrA-activated genes (yibD, pmrAB, cptA, etc.) or were genes located in the local region around preA, including the preAB operon. The transcriptional units were defined in this local region by RT-PCR, suggesting three PreA activated operons composed of preA-preB, mdaB-ygiN, and ygiW-STM3175. Several putative virulence-related phenotypes were examined for preAB mutants, resulting in the observation of a host cell invasion and slight virulence defect of a preAB mutant. Contrary to previous reports on this TCS, we were unable to show a PreA/PreB-dependent effect of the quorum-sensing signal AI-2 or of epinephrine on S. Typhimurium with regard to bacterial motility. CONCLUSION: This work further characterizes this unorthadox OmpR/EnvZ class TCS and provides novel candidate regulated genes for further study. This first in-depth study of the PreA/PreB regulatory system phenotypes and regulation suggests significant comparative differences to the reported function of the orthologous QseB/QseC in E. coli.